PENINGKATAN PERTUMBUHAN DAN HASIL CABAI BESAR (Capsicum annum L) MELALUI PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT DAN PUPUK HAYATI PADA TANAH PODSOLIK - Ramince Ramince; Zubaidah S (AgriPeat, 2015)
This study aimed to determine the effect of compost oil palm empty fruit bunches and Biological Fertilizer on growth and yield great chili. The study was conducted in March-August 2014 at Jl. G. Obos 26, Kereng Bangkirai, Sebangau, Palangkaraya, This study used a completely randomized design (CRD) with two-factor factorial treatment. The first factor was the EFB compost consisting of 4 levels, namely: K0 = Without giving TKKS (0 g polybag-1); K1 = Giving TKKS (10.57 g polybag-1); K2 = Giving TKKS (21.14 g polybag-1); K3 = Giving TKKS (31.71 g polybag-1). The second factor was the provision of Biological Fertilizer (M) which consists of 4 levels, namely: M0 = Without giving Miza Plus (0 g polybag-1); M1 = Miza Plus (5.28 g polybag-1); M2 = Miza Plus (10.57 g polybag-1); M3 = Miza Plus (15.85 g polybag-1), so there are 16 combinations of treatment and repeated three times so that there are 48 units experiment. The results showed that there was an interaction on plant height and age 6 WAP and flower emergence occurred real influence number of productive branches, number of fruit and fresh fruit weight. The highest yield of fresh fruit heavy large pepper plants contained in a single treatment makes no compost TKKS K3 = (31.71 g polybag-1) and not significantly different with K2 = (21.14 g polybag-1), K1 = (10.57 g polybag-1); and the highest yield on a single factor giving Biological Fertilizer M2 (10.57 g polybag-1) and not significantly different from M3 = (15.85 g polybag-1)